„Quae tibi quaerebam (…) dona Tomitanus mittere posset ager” – o pewnym podarunku znad Pontu (Wokół „Ex Ponto” III 8) - Puk, Marlena (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2023)
Among the topics discussed by Ovid in Tristia and Epistulae ex Ponto, there is also the topic of gifts. The poet plays the role of both the recipient and the person who can give something to his addressees. In the vast majority of cases, the gifts mentioned are not specific objects, but have an intangible value: the poet perceives the life left to him in terms of a gift, as well as the memory and consolation shown to him by his relatives. He himself wishes to repay the favours received and promises his correspondents eternal fame by including their names in his songs. The Ex Ponto III 8 elegy is unique in this topic. First, Naso notifies the addressee about a material gift sent to him, and secondly, the very gift he decided to offer to his friend is remarkable: a quiver filled with poisoned arrows. Such a gift also played a double role: on the one hand, it reflected the conditions in which the poet found himself, it was, according to his message, the only thing that could be found in Tomis and sent to Rome; on the other hand, it was to serve the recipient to defend himself against his personal enemies. The source texts testify that the arrows dipped in a specific poison were used by the Scythians. The frequency and nature of the mention of this doubly dangerous weapon in both collections of Ovid’s exile poetry, and finally the decision to make it the only material gift sent to the capital, prompted the author of this text to propose a thesis about Ovid’s peculiar fascination with Scythian poisoned arrows.